Methyl‐Sensing Nuclear Receptor Liver Receptor Homolog‐1 Regulates Mitochondrial Function in Mouse Hepatocytes. Issue 3 (23rd December 2019) - Choi, Sungwoo; Dong, Bingning; Lin, Chih‐Chun Janet; Heo, Mi Jeong; Kim, Kang Ho; Sun, Zhen; Wagner, Martin; Putluri, Nagireddy; Suh, Jae Myoung; Wang, Meng C.; Moore, David D.
Abstract : Background and Aims: Liver receptor homolog‐1 (LRH‐1; NR5A2) is a nuclear receptor that regulates metabolic homeostasis in the liver. Previous studies identified phosphatidylcholines as potential endogenous agonist ligands for LRH‐1. In the liver, distinct subsets of phosphatidylcholine species are generated by two different pathways: choline addition to phosphatidic acid through the Kennedy pathway and trimethylation of phosphatidylethanolamine through phosphatidylethanolamine N ‐methyl transferase (PEMT). Approach and Results: Here, we report that a PEMT–LRH‐1 pathway specifically couples methyl metabolism and mitochondrial activities in hepatocytes. We show that the loss of Lrh‐1 reduces mitochondrial number, basal respiration, beta‐oxidation, and adenosine triphosphate production in hepatocytes and decreases expression of mitochondrial biogenesis and beta‐oxidation genes. In contrast, activation of LRH‐1 by its phosphatidylcholine agonists exerts opposite effects. While disruption of the Kennedy pathway does not affect the LRH‐1‐mediated regulation of mitochondrial activities, genetic or pharmaceutical inhibition of the PEMT pathway recapitulates the effects of Lrh‐1 knockdown on mitochondria. Furthermore, we show that S ‐adenosyl methionine, a cofactor required for PEMT, is sufficient to induce Lrh‐1 transactivation and consequently mitochondrial biogenesis. Conclusions: A PEMT–LRH‐1 axis regulates mitochondrial biogenesis and beta‐oxidation in hepatocytes.